1977
DOI: 10.1042/bj1640389
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of phytohaemagglutinin and of calcium ionophore A23187 on the metabolism of glycerolipids in small lymphocytes

Abstract: 1. The effects of phytohaemagglutinin and of a Ca2+ ionophore (A23 187) on glycerolipid metabolism in lymphocytes from pig lymph nodes were compared (a) by studying the incorporation of [32P] Phytohaemagglutinin only stimulated 32p incorporation into phosphatidylinositol and, to a slight extent, phosphatidate. Removal of most of the extracellular Ca2+ somewhat decreased this response. 3. lonophore A23187 stimulated the labellingofphosphatidateand phosphatidylinositol with 32p to a much greater extent than did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

1978
1978
1992
1992

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Diacylglycerol from this source could be a substrate for phosphatidic acid formation. A Ca2+-sensitive triacylglycerol lipase has previously been demonstrated in human neutrophils and lymphocytes (Allan & Michell, 1977).…”
Section: Discussionmentioning
confidence: 93%
“…Diacylglycerol from this source could be a substrate for phosphatidic acid formation. A Ca2+-sensitive triacylglycerol lipase has previously been demonstrated in human neutrophils and lymphocytes (Allan & Michell, 1977).…”
Section: Discussionmentioning
confidence: 93%
“…Triacylglycerols, phosphatidic acid or other phospholipids could also be precursors of diacylglycerol. Evidence that vasopressin or Ca2 + affect some of the reactions involved in the conversion of these lipids into diacylglycerol has been obtained (Allan & Michell, 1977;Williamson et al, 1980;Sugden & Williamson, 1981;Alemany et al, 1982;Pollard & Brindley, 1984). Comparison of the fatty acid composition of the diacylglycerols formed in the presence of vasopressin with that of triacylglycerols (Akesson, 1969), the observations that vasopressin increases the rate of fatty acid esterification (Williamson et al, 1980) and the amount of [32P]phosphatidic acid in cells prelabelled with [32P]P; (Thomas et al, 1983;Litosch et al, 1983), and the failure of glucagonwhichlhas been shown to alter hepatic triacylglycerol metab-olism (reviewed by Saggerson & Bates, 1981;Pelech et al, 1983)] to induce a transient change in diacylglycerols suggest that stimulation by vasopressin of the net conversion of triacylglycerol or phosphatidic acid into diacylglycerol is unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced phosphatidylinositol labelling can also occur: (a) when any other lipid breaks down to yield diacylglycerol which can then be converted to phosphatidate and phosphatidylinositol (e.g. triacylglycerol breakdown in response to cytosolic Ca2+; Allan & Michell, 1977); or (b) when synthesis of phosphatidylinositol de novo is enhanced (e.g. during the redirection of lipid synthetic pathways in cells exposed to amphiphilic cations; Brindley et al, 1975).…”
Section: Blc -L Ettersmentioning
confidence: 99%